Implementation of Small Game Modifications as a Form of Warm-Up to Student’s Interest in Physical Education Learning at MAN 1 Musi Banyuasin - Jauhari, Pebi; Lian, Bukman; Imansyah, Farizal (Yayasan Sembilan Pemuda Indonesia, 2023)
Warm-up activities are important activities before students carry out core activities in physical education learning, but since the covid 19 last year physical education learning has been forced to be carried out online, and when learning is carried out offline, many of the students do not look serious and lazy on the grounds that warm-up activities are just that, and there is no challenge when doing warm-up activities during learning and boring; therefore, there is a need for small game modifications when doing warm-up activities so that students are interested in participating in physical education learning. Therefore, this study aimed to determine the implementation of small game modifications as a form of warm-up to students’ interest in learning Physical Education. The population comprised 150 class XII MAN 1 Musi Banyuasin individuals. The sample in this study consisted of 35 students who were recruited using the cluster random sampling technique. This study used an experimental method. A questionnaire with 20 statements was used for data collection. Validity and reliability were tested by experts using a questionnaire with 20 statement items. Validity and reliability testing using validity tests by experts. The results showed that there was a significant effect on the implementation of small game modifications as a form of warm-up on student interest in learning physical education, as evidenced by the results of student answers through distributing questionnaires of overall student answers from questionnaires no. 1-20 on average, students answered that they agreed with a total of 269. The lowest number of student answers strongly disagreed, with a total of 23.